Word, Lexeme, Word Form in Uzbek Linguistics (Word Form), A Question About the Form of a Word - Abdullayev Jumanazar Xudoyberdiyevich (Genius Journals, 2023)
The article criticizes the use of the term word in Uzbek linguistics instead of lexical units with lexical meaning – lexeme and lexico-grammatical unit, as well as morphological unit –word form, provides scientific justification for the need for their differentiation, gives the main solution to the problem – the general definition of the word
Keywords: Word; lexeme; word form; morpheme